Comparison of subomohyoid plane block and interscalene nerve block for arthroscopic shoulder surgery - Rabab S. S Mahrous; Tarek I Ismail (Egyptian Journal of Anaesthesia, 2022)
Background Ultrasound guided interscalene nerve block (ISB) is a popular procedure for pain relief in shoulder surgery patients. The subomohyoid plane block is a new reliable and technically easy regional technique that can be properly used for pain management with fewer adverse effects. The aim of this study was to validate whether there is a difference in postoperative pain scores and morphine consumption between interscalene and subomohyoid plane blocks.Method Eighty patients scheduled for shoulder arthroscopy were enrolled in this controlled blinded study and randomized to interscalene or subomohyoid plane blocks using 15 ml 0.5% bupivacaine in each group and general anesthesia. The primary outcome was pain severity at rest using VAS. Secondary outcomes were first 24 h total morphine consumption, patient satisfaction and adverse effects.Results All patients completed the study through the primary outcome analysis. VAS scores at PACU 2 h were similar in both groups, and VAS scores at 4, 8, 12,18 and 24 h were statistically lower in the interscalene block group (ISB) than in the subomohyoid group (p < 0.001), with no clinical significance. Total morphine consumption was lower in ISB group than in the subomohyoid group (p < 0.001). Time to the first rescue analgesic request and patients’ satisfaction were similar in both groups. Ipsilateral phrenic nerve was blocked in 37.5% of patients in ISB group vs. 7.5% in the subomohyoid group (p < 0.001).Conclusion Subomohyoid plane block can be considered as an alternative to interscalene block for shoulder arthroscopy surgery.